2017
DOI: 10.1175/mwr-d-16-0453.1
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Radar Metrics Related to Tornado Life Cycles and Intensity in Supercell Storms

Abstract: Polarimetric radar signatures have been related to the typical evolution of supercell storms, including through tornado life cycles. Now that polarimetric radar observations are available for a large sample of supercell storms, time series of new radar metrics can be derived. These metrics can be compared with phases of known tornado life cycles in an effort to develop new methods of anticipating tornadoes and to increase understanding of storm-scale structural and microphysical changes through supercell and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…To date, research has demonstrated that Z DR columns likely provide useful information about storm intensity and potential threats, but little clear information exists to connect them directly to existing conceptual models and warning decisions, thereby limiting a forecaster's ability to leverage the full benefits of dual-pol technology during severe-weather operations (e.g., Kumjian and Ryzhkov 2008;Kumjian 2013). Knowledge gaps also exist regarding Z DR column evolution in nontornadic supercells, column evolution across multiple elevation angles (i.e., volumetric analysis), impact of radar update time on accurate sampling of column evolution, and typical values of Z DR column depth (e.g., Van Den Broeke et al 2008;Picca et al 2015;Van Den Broeke 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has demonstrated that Z DR columns likely provide useful information about storm intensity and potential threats, but little clear information exists to connect them directly to existing conceptual models and warning decisions, thereby limiting a forecaster's ability to leverage the full benefits of dual-pol technology during severe-weather operations (e.g., Kumjian and Ryzhkov 2008;Kumjian 2013). Knowledge gaps also exist regarding Z DR column evolution in nontornadic supercells, column evolution across multiple elevation angles (i.e., volumetric analysis), impact of radar update time on accurate sampling of column evolution, and typical values of Z DR column depth (e.g., Van Den Broeke et al 2008;Picca et al 2015;Van Den Broeke 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Z DR data from the WSR-88D were calibrated following the procedure of [29], which is also applied by [17,30]. From the radar dataset, the low-level scan nearest the midpoint of the disdrometer dataset was selected (~2206 UTC) and all pixels~1.5 km above the ambient 0 • C level in convective anvil regions with 20 dBZ ≤ Z HH ≤ 35 dBZ were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Atmosphere 2020, 11, x FOR PEER REVIEW 4 of 18 ZDR data from the WSR-88D were calibrated following the procedure of [29], which is also applied by [17,30]. From the radar dataset, the low-level scan nearest the midpoint of the disdrometer…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize all that has been said, I want to express the hope that my vision of the nature of the tornado will eventually "curb" this formidable phenomenon, and not only endlessly study its features, as is now happening [17][18][19].…”
Section: Main Bodymentioning
confidence: 99%